Model Experiential Learning Dalam Pembelajaran Menulis Laporan Pengamatan Siswa Bagi Kelas V Sekolah Dasar - Aulia, Pertiwi; Taufik, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to improve the skills of writing student observation reports with experiential learning models for fifth-grade students of SDN 05 Air Tawar Barat at the pre-writing, writing and post-writing stages. This type of research is Classroom Action Research using qualitative and quantitative approaches. The research subjects were teachers and fifth-grade students of SDN 05 Air Tawar Barat with data collection techniques in the form of observation and portfolio assessment. The results of the study indicate an increase in the implementation and student learning outcomes. Assessment of the implementation of teacher activities in the first cycle averaged 75%, in the second cycle an average of 92.9%. Assessment of the implementation of student activities in the first cycle averaged 75%, in the second cycle an average of 92.9%. The results of the recapitulation of student scores in the first cycle with a class average of 74.9%, in the second cycle the results of the recapitulation were 83.7%. Thus it is stated that the experiential learning model can improve the writing skills of student observation reports.